Consciousness after split-brain surgery: The recent challenge to the classical picture. (17th September 2021) - Schechter, Elizabeth; Bayne, Tim
Abstract: In a recent series of experiments, Pinto and colleagues found that the split-brain patient D.D.C. was able to respond accurately to stimuli in either visual field, whether using his right hand, his left hand, or verbally. Pinto and colleagues argue that this demonstrates that a split-brain patient remains a unitary agent and thus continues to possess a unified consciousness. This paper provides a critical evaluation of that claim. First, we argue that two conceptions of the unity of consciousness need to be distinguished: an agency-based conception and an experience-based conception. Second, we argue that it is an open question whether the data presented by Pinto and colleagues is best understood in terms of the unity of agency. Whether that interpretation is correct depends not only on the mechanisms that produce split-brain behaviour, but also on what is involved in being a single agent. Third, we argue that even if the behavioral data indicated that D.D.C has a unified consciousness in the agency-based sense of the term, it is difficult to reconcile them with the claim that his consciousness is fully unified in the experience-based sense. Highlights: There are 3 possible mechanisms of crossed responses after split-brain surgery. In Pinto et al.'s study it is unclear which mechanisms operated in D.D.C. There are two conceptions of conscious unity: agentive and experiential. It is uncertain whether patient D.D.C. has a unified consciousness in either sense. Split-brain consciousness may be partially unified.